Severity of persistent pain and disability can accurately screen for presence of pain catastrophizing and fear of performing wrist movements in individuals with distal radius fracture. (February 2022) - Mahdavi, Mohammad; Farzad, Maryam; Mehta, Saurabh P.; MacDermid, Joy C.; Vahedi, Mohsen; Hosseini, Seyed Ali; Shafiee, Erfan; Farhoud, Amir Reza
Abstract: Background: The evidence indicating presence of psychological factors concerns in individuals who report persistent residual pain and disability over a longer term after distal radius fractures (DRF) is emerging but requires further inquiry. Objectives: To examine the associations of persistent wrist pain and disability at 6-months after DRF with the presence of psychological factors. Methods: Eighty-five patients with DRF were evaluated for wrist pain and disability with subscales of Patient-rated wrist evaluation (PRWE), 6-months after the fracture. The associations of wrist pain and disability with these psychological factors at 6-months after DRF were examined using multivariable logistic regression models. The ability of PRWE scores at 6-months after DRF to accurately classify individuals with and without these psychological factors was examined using the area under the receiver operating characteristic curve (AUC). Results: Higher PRWE-P scores were significantly associated with worse pain catastrophizing, having emotional distress, and fear of performing wrist movements. In addition, higher PRWE-F scores were also highly associated with worse pain catastrophizing, having emotional distress, and fear of performing wrist movements. The PRWE-P or PRWE-F Scores of ≥18/50 showed the best combination of sensitivity and specificity in identifying individuals with pain catastrophizing, emotional distress, and fear of performing wrist movements at 6-months after DRF (AUC values of ≥0.88). Conclusion: The novel finding of this study is that scores of ≥18/50 PRWE-P or PRWEF can be used to screen for the presence of these psychological factors. Highlights: DRFs with residual symptoms should be screened for psychological factors. Symptomes are associated with pain catastrophizing, depression, fear of movements. PRWE ≥18 after DRF indicate pain catastrophizing, depression, fear of movements.